Pemberdayaan Kelompok Tani Sayuran melalui Intensifikasi Ekologi Menggunakan Eko-Teknologi Non-Mikroba di Sekitar Kebun Raya Kendari - Laode Muhammad Harjoni Kilowasidi; Robiatul Adawiyah; Nur Isiyana Wianti (Institut Pertanian Bogor, 2022)
Agricultural Innovation in the green revolution contains high ecological risk, so that eco-technology innovation is needed for the sustainability of agricultural productivity. Unfortunately, not all farmers know about of this innovation, including members of the Nanga-Nanga Makmur Farmers Group around the Kendari City Botanical Gardens. This Community Partnership Program aimed to: (i) increase the knowledge and skills of target farmers regarding the management of abundant organic waste around farmers' fields to be used as non-microbial biofertilizer products; and (ii) provide knowledge to target farmers about conducting soil quality testing as a reference for farmers to determine the dose of non-microbial biofertilizer on managed agricultural land by members of the farmer groups. The method applied to achieve this goal is to do incidental counseling through face-to-face activities, training activities through mentoring in plot demonstration actions. Data on the increasing knowledge and skills of farmers were recorded through photos during mentoring and pilot demonstrations and analyzed descriptively. The results of these activities have increased the knowledge and skills of farmers in evaluating soil fertility using KIT for soil analysis, and determining the need for organic matter and fertilizers. Partner farmers have been able and skilled to produce biochar, compost tea, and compost as non-microbial biofertilizer by utilizing liquid organic waste and organic solid waste. Farmers can to manage soil quality and plant health through the application of non-microbial biofertilizer to soil and plants. Farmers also have insight into pest/disease control through an eco-technology approach.